2019
DOI: 10.1186/s13023-019-1031-7
|View full text |Cite
|
Sign up to set email alerts
|

High penetrance of acute intermittent porphyria in a Spanish founder mutation population and CYP2D6 genotype as a susceptibility factor

Abstract: Background Acute intermittent porphyria (AIP) is a low-penetrant genetic metabolic disease caused by a deficiency of hydroxymethylbilane synthase (HMBS) in the haem biosynthesis. Manifest AIP (MAIP) is considered when carriers develop typical acute neurovisceral attacks with elevation of porphyrin precursors, while the absence of attacks is referred to as latent AIP (LAIP). Attacks are often triggered by drugs, endocrine factors, fasting or stress. Although AIP penetrance is tradition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 32 publications
(35 reference statements)
0
12
0
Order By: Relevance
“…Cyp21a1, the homolog of human CYP21A2 or CYP17A1 (-37), is a crucial enzyme in corticosteroid and sex hormone synthesis; Cyp21a1 is downregulated in mice with induced AIP but upregulated in wild-type mice (88,89). A study based on the population in the Spanish region of Murcia revealed parallel findings: the alleles CYP2D6*4 and *5 may prevent acute attacks in patients with AIP while CYP2D6 may constitute a penetrance-modifying gene (26).…”
Section: Cytochrome P450 Genementioning
confidence: 97%
See 1 more Smart Citation
“…Cyp21a1, the homolog of human CYP21A2 or CYP17A1 (-37), is a crucial enzyme in corticosteroid and sex hormone synthesis; Cyp21a1 is downregulated in mice with induced AIP but upregulated in wild-type mice (88,89). A study based on the population in the Spanish region of Murcia revealed parallel findings: the alleles CYP2D6*4 and *5 may prevent acute attacks in patients with AIP while CYP2D6 may constitute a penetrance-modifying gene (26).…”
Section: Cytochrome P450 Genementioning
confidence: 97%
“…Due to founder effects, the prevalence of AIP was markedly higher in some regions, such as 17.7 per million in southeastern Spain (26) and 23 per million in Sweden (19). In northern Sweden, it was even 192 per million (27).…”
Section: Prevalence and Penetrance Of Aipmentioning
confidence: 99%
“…Such is the case with the HMBS pathogenic variant NM_000190.3( HMBS ):c.669_698del30 p.(Glu223_Leu232) in the Region of Murcia, south-east Spain [ 3 ]. As a consequence, AIP prevalence has increased in this part of the country [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although precipitating factors can trigger acute attacks, unknown modifying genes and/or epigenetic factors are likely to be largely responsible for the pathological phenotype. 13,14 Common precipitants of acute attacks include medications and other chemicals (see network resources), excess alcohol intake, certain steroid hormones, acute illness, infection, stress, physical exhaustion, caloric deprivation and rapid weight loss. These factors are all linked through the induction of hepatic ALAS1 mRNA expression, either directly or via PGC1a (e.g.…”
Section: Acute Hepatic Porphyriasmentioning
confidence: 99%